GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Synergistic cooling effects of UV protective shading and PV-ESS powered ventilation on pedestrian-level microclimate and modelled physiological heat stress - Shisheng Chen; Weiwei Yang; Jiayan Fu; Zhongqi Yu; Yumeng Jin; Meng Zhen; Lei Xu; Ruohan Xu; Chao Cen (Building and Environment, 2026)

Co-mitigating tire wear particles and their leachates across the life cycle: A critical review - Kejun Liao; Junyi Yu; Ruohan Huang; Wenjing Zhou; Yuwei Zhou; Junru Guo; Shengman Zhang; Chen Cai; Kaiming Peng; Xiangfeng Huang; Jia Liu (Water Research, 2026)

Application of POD-ANN reduced order model to fluid-thermal-structural coupling analysis in printed circuit heat exchangers - Hanxing Liu; Minyun Liu; Shenghui Liu; Yu Tang; Ruilong Liu; Junjie Fei; Yuanfeng Zan; Ruohan Zheng; Yanping Huang (Annals of Nuclear Energy, 2026)

Transformer-Enhanced Instance Segmentation for Automated Crucian Carp Phenotyping Under Controlled Imaging Conditions - Miao Zhu; Ruohan Lu; Yi Zhou; Sisi Yuan; Qiu Xiao; Yu Deng (Fishes, 2026)
Fish phenotyping plays an important role in growth evaluation, selective breeding, and precision aquaculture. Conventional phenotypic measurement methods are labor-intensive, time-consuming, and susceptible to observer variability. To improve measurement efficiency and reproducibility, this study proposes an automated fish phenotyping framework based on Transformer-enhanced instance segmentation. Specifically, a Mask2Former decoder was integrated into the Mask R-CNN architecture to improve boundary delineation and segmentation quality. Based on segmentation outputs, phenotypic parameters, including body length, body height, and projected area, were automatically extracted using PCA-assisted orientation estimation and geometric measurement. In addition, a standardized anatomical landmark annotation framework consisting of 12 reference points was introduced to support reproducible phenotypic description and future extensible morphometric analysis. Body weight was further estimated using polynomial regression based on extracted morphological traits. Experiments were conducted using images from three crucian carp varieties under controlled imaging conditions. The proposed framework achieved 92.7% mAP and 89.4% Boundary IoU, improving segmentation performance over the baseline model. Automated measurement yielded average relative errors of 2.16% for body length and 3.85% for body height, while weight prediction achieved an R2 of 0.9479 and a mean relative error of 7.31%. These results demonstrate that Transformer-enhanced segmentation can support accurate and efficient automated phenotyping under standardized conditions and provide a foundation for future deployment in more complex aquaculture environments.

Combined organic pollutants and heavy metals distinctly alter microbial assembly and metabolism of Cynodon dactylon (L.) Pers. within industrial green belts - Junyi Yu; Shuangqiang Li; Junru Guo; Ruohan Huang; Chen Cai; Kaiming Peng; Lijun Lu; Xiangfeng Huang; Jia Liu (Journal of Environmental Sciences, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Analysis of the blowdown of supercritical carbon dioxide from simple vessel - Fengyuan Tian; Minyun Liu; Yanping Huang; Ruohan Zheng; Yangle Wang; Houjun Gong; Yu Tang; Tianzeng Liu; Jinghan Hu; Haohan Yuan; Yuan Zhou (Annals of Nuclear Energy, 2026)

Quantifying key design factors for thermal comfort in underground space through global sensitivity analysis and machine learning - Shisheng Chen; Nyuk Hien Wong; Chao Cen; Ruohan Xu; Lei Xu; Zhenjiang Shen; Zhigang Wu; Jiayan Fu; Zhongqi Yu (Tunnelling and Underground Space Technology, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

A novel TpAQ-COF/ZnS/ZnIn2S4 ternary photocatalyst with double Z-scheme heterostructure for visible light photocatalytic degradation of 2,4-dichlorophenol - Ruohan Sun; Yuqing Xia; Tingting Ma; Hui Yu; Guixia Liu; Jinxian Wang; Wensheng Yu; Feng Sun; Xiangting Dong (Journal of Cleaner Production, 2026)

Rice protein-based gel particles for Pickering emulsion - Peifeng Lv; Qianyu Ye; Yong Wang; Like Mao; Ruohan Yu; Cordelia Selomulya (Food Hydrocolloids, 2025)

Surface nitridation of Si enabled gradient artificial solid electrolyte interface and self-optimized structural evolution - Zhenyi Huang; Ruohan Yu; Jinshuai Liu; Yuxia Zhong; Lei Zhang; Liang Zhou (Science Bulletin, 2025)

Dynamics of wall bubbles in flash evaporation systems: Heterogeneous expansion and microlayer development - Qifan Wang; Junren Hou; Shanfang Huang; Fangbei Chen; Minyun Liu; Ruohan Zheng; Yanping Huang; Lie Quan; Houjun Gong; Yu Tang (Annals of Nuclear Energy, 2025)

Lab on a single microbead: An enzyme-free strategy for the sensitive detection of microRNA via efficient localized catalytic hairpin assembly - Yan Qi; Jiangtao Yu; Ming Lou; Yameng Yu; Ruohan Li; Zhenhao Zhang; Yuxuan Dai; Kejing Lao; Meng Cao; Xingchun Gou (Analytica Chimica Acta, 2025)

The combined effects of microplastics and their additives on mangrove system: From the sinks to the sources of carbon - Junru Guo; Mingqing Yang; Ruohan Huang; Junyi Yu; Kaiming Peng; Chen Cai; Xiangfeng Huang; Qiaofeng Wu; Jia Liu (Science of The Total Environment, 2025)

Hyaluronic acid modulates gut microbiota and metabolites relieving inflammation: A molecular weight-dependent study - Chuan Zhang; Botao Wang; Leilei Yu; Ruohan Zhao; Qingsong Zhang; Chengcheng Zhang; Shumao Cui; Jianxin Zhao; Arjan Narbad; Wei Chen; Fengwei Tian; Qixiao Zhai (Science Bulletin, 2024)

Research on precise phenotype identification and growth prediction of lettuce based on deep learning - Haiye Yu; Mo Dong; Ruohan Zhao; Lei Zhang; Yuanyuan Sui (Environmental Research, 2024)

Operation-friendly and accurate naked-eye observation assay for fast zoonotic echinococcosis and pulmonary tuberculosis monitoring in clinics - Hong Liang; Ruohan Wang; Tianying Luo; Mengying Yuan; Xia He; Rongrong Jin; Yangyang Zhao; Rongsheng Tong; Yu Nie (Analytica Chimica Acta, 2024)

Integrated analysis of miRNAs, transcriptome and phytohormones in the flowering time regulatory network of tea oil camellia - Haixiao Fan; Xiaoling Wang; Huiqi Zhong; Kehui Quan; Ruohan Yu; Shiying Ma; Siqiong Song; Mengfei Lin (Physiology and Molecular Biology of Plants, 2024)

A DEM-based approach for modeling the thermal-mechanical behavior of frozen soil - Ruohan Sun; Run Liu; Huan Zhang; Rui Zhang; Yu Jiang; Ruilong Yin (European Journal of Environmental and Civil Engineering, 2024)

Characterization of carbonaceous particles by single particle aerosol mass spectrometer in the urban area of Chengdu, China - Junke Zhang; Rui Wang; Chunying Chen; Yunfei Su; Luyao Chen; Wei Zhang; Yingwei Xi; Yangchun Yu; Ruiyan Pu; Minghui Lu; Ruohan Wu; Xuhui Shen (Environmental Science and Pollution Research, 2024)

A critical review on selenium removal capacity from water using emerging non-conventional biosorbents - Habib Ullah; Baoliang Chen; Audil Rashid; Ruohan Zhao; Asfandyar Shahab; Guo Yu; Ming Hung Wong; Sangar Khan (Environmental Pollution, 2023)

Uncovering the origin of surface-redox pseudocapacitance of molybdenum phosphides enables high-performance flexible sodium-ion capacitors - Yalong Jiang; Runya Han; Jun Dong; Ruohan Yu; Shuangshuang Tan; Fangyu Xiong; Qiulong Wei; Junjun Wang; Lianmeng Cui; Haiyang Tian; Yingkui Yang; Qinyou An (Chemical Engineering Journal, 2023)

Anisotropic In-Plane strain engineering Ni(OH)2 to activate alkaline hydrogen evolution reaction - Wenda Zhong; Ruohan Yu; Weilong Cao; Le Sun; Yi Yang; Ingo Manke; Chao Yang; Kangning Zhao (Chemical Engineering Journal, 2023)

Solution-catalyzed carbothermal reduction of argo-waste SiO2 enables low-temperature and fast synthesis of Si(Ⅱ)-C anode - Zi'ang Liu; Ruohan Yu; Shaohua Zhu; Jiashen Meng; Xuanpeng Wang; Chaojiang Niu; Lianmeng Cui; Fan Qiao; Junjun Wang; Liqiang Mai (Chemical Engineering Journal, 2023)

Local site effect of soil-rock ground: 1-g shaking table test - Yong Yuan; Siming Li; Haitao Yu; Mingqing Xiao; Ruohan Li; Ruozhou Li (Bulletin of Earthquake Engineering, 2023)

In vitro fermentation of heparin by the human gut microbiota: Changes in the microbiota community and metabolic functions - Chuan Zhang; Leilei Yu; Qixiao Zhai; Ruohan Zhao; Jianxin Zhao; Hao Zhang; Wei Chen; Fengwei Tian (Food Chemistry, 2023)

Structural architecture of Neoproterozoic rifting depression groups in the Tarim Basin and their formation dynamics - Bizhu He; Cunli Jiao; Taizhu Huang; Xingui Zhou; Zhihui Cai; Zicheng Cao; Zhongzheng Jiang; Junwen Cui; Zhuoyin Yu; Weiwei Chen; Ruohan Liu; Xiaorui Yun; et al. (Science China Earth Sciences, 2019)

Constant hypoxia inhibits osteoclast differentiation and bone resorption by regulating phosphorylation of JNK and IκBα - Zhenzhen Ma; Ruohan Yu; Jinxia Zhao; Lin Sun; Leilei Jian; Changhong Li; Xiangyuan Liu (Inflammation Research, 2019)